Czech adult learners' beliefs about how best to approach learning English as a foreign language (Masaryk University Internationalization Programme) - Špatková, Petra (2007)
The thesis was written in order to examine Masaryk University Internationalization learners' beliefs about learning English as a foreign language. The theoretical section introduces the concept and classification of learner beliefs. The research deals with quantitative data derived from the questionnaire administered to seventy-three participants who took part in the Masaryk University Internationalization Programme. Their responses were analysed and suggestions for further research were discussed